Evaluation of the Impact of a Student Pharmacist–Supported Program to Improve Hospital-Based Quality Measures. (April 2016) - Bergman, Brandon; Wrin, Justin; Kaakeh, Yaman
Background. Although previous studies have demonstrated positive impact of student pharmacists on clinical interventions, no published studies to date have demonstrated the specific impact of student pharmacists on improving National Hospital Inpatient Quality Measures (NHIQM).Objective. To evaluate the impact of a student pharmacist–supported program targeted at improving the venous thromboembolism (VTE) quality measures set forth by the NHIQM.Methods. Retrospective review of VTE quality measure compliance at a community nonteaching hospital. During this time, student pharmacists supported a VTE prophylaxis program that evaluated admitted patients for chemical or mechanical prophylaxis needs. Compliance to VTE quality measures were also evaluated by a trained medical data abstractor based on criteria given by the Joint Commission.Results. Four major NHIQM criteria for VTE were selected for evaluation. National and state averages were compared to the overall hospital averages across various timeframes. The student-supported program demonstrated consistently high performance for the VTE-1 and VTE-5 measures.Conclusion. Student pharmacists have opportunities in improving inpatient quality measures and can play a significant role in patient care through thorough evaluation and intervention.